Depression and Its Risk Factors Among Patients with Chronic Obstructive Pulmonary Disease (COPD) in a Tertiary Level Hospital (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: COPDis accompanied with several co-morbidities among which depression is a major one. The aim of the study is to assess the prevalence of depression and associated risk factors in patients with COPD in a tertiary level hospital of Dhaka city, Bangladesh.Method: This Cross-sectional study was carried out the Department of Respiratory Medicine of ShaheedShurawardy Medical College Hospital from January 2014 to June 2014. 317 COPD patients were selected by systematic sampling. A questionnaire was administered among the respondents to collect the data regarding their socio-demographic conditions followed by Patient Health Questionnaire 9 (PHQ-9) to measure the level of depression.Result: Among the 317 respondents, the mean age was 58.40 and 98.1% were male, 1.9% were female. The proportion of depression among patients with COPD was 81.6% (8 out of 10 COPD patients). Among the all respondents, 23.3% had moderate depression, 14.5% had moderately severe depression, and only 4.7% had severe depression. The risk factors which were found to be involved with the development of depression among COPD patients were stage 2 and stage 3 COPD, onset of COPD ? 40 years of age, literate respondents.Conclusion: The study highlight the importance of routine screening for depression of all COPD patients in all healthcare settings and implementation of strategies for proper management and prevention of depression in those patients.J Shaheed Suhrawardy Med Coll, December 2015, Vol.7(2); 44-48